Thermally Tunable Absorption‐Induced Transparency by a Quasi 3D Bow‐Tie Nanostructure for Nonplasmonic and Volumetric Refractive Index Sensing at Mid‐IR. Issue 6 (9th March 2016) - Hasan, Dihan; Ho, Chong Pei; Lee, Chengkuo
Abstract : A nonresonant transmission process namely absorption‐induced transparency (AIT) is demonstrated in a quasi 3D bow‐tie nanostructure at mid‐IR spectrum for the first time. The quasi 3D structure is formed by self‐aligning two metasurfaces obtained by the Babinet's principle which are linked to each other through a patterned layer of PMMA. It is shown that the vibrational absorption of poly(methyl methacrylate) (PMMA) at 5.79 μm can strongly influence the propagation characteristics of the quasi 3D structure and generate the absorption‐induced transmission peak. A detailed parametric study is conducted on the process and its nonplasmonic characteristics are confirmed. Later, the usefulness of the quasi 3D nanochannels of the geometry is addressed and volumetric refractive index sensing (refractive index unit (RIU) shift of 123.33 nm) by the AIT effect is experimentally demonstrated for the first time. Lastly, the thermal responsiveness of the metal–dielectric hybrid platform is exploited and a thermal tuning up to 25 nm for a moderate range of temperature increase (100°) is obtained. It is believed that the hybrid system with 3D nanochannels assisted transparency can be a new avenue for volumetric plasmonic sensing and stimuli responsive device operating solely on the principle of changing molecular conformation of material. Abstract : A nonresonant transmission process namely absorption‐induced transparency (AIT) at mid‐IR wavelength range is reported. Thanks to the myriad of vibrational finger prints at mid‐IR, a plasmonic device that is sensitive to a wide range of stimulation, e.g., temperature, humidity, pH, and UV irradiation, can be implemented by entirely relying on the conformational change of the molecular modes in exotic materials.